Implementasi Inovasi Ebook IPA Interaktif Berbasis Project Based Learning (PjBL) untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik SMP - Musdalifah Musdalifah; Asri Widowati; Suyanta Suyanta; Sabar Nurohman; Sri Rejeki (Jurnal Penelitian Pendidikan IPA, 2023)
The ability to think critically is one of the profiles of Pancasila students that students must possess in the independent curriculum. Critical thinking skills are one of the abilities that students need in solving problems. This research aims to describe the implementation of interactive Science ebooks based on PBL to enhance the critical thinking skills of students in the topic of environmental pollution. The research design used is quantitative descriptive. The research design used a one-group pretest-posttest design. The population of the study is all seventh-grade students of SMPN in Yogyakarta. The sample of this research is the seventh-grade student’s one of the junior high schools in Yogyakarta, selected through simple random sampling technique. The research instrument used is a multiple-choice critical thinking test with five indicators. Indicators of critical thinking abilities are explaining, evaluation, concluding, analysis, and designing strategies. The results showed an improvement in critical thinking skills through the N-gain test of 0.8, indicating a high category. The average indicator of students' critical thinking skills who obtained the highest score was the explaining indicator with an average of 90.5%, while the indicator with the lowest average among students' critical thinking skills was the analysis indicator with an average of 70.01%. This indicates that the use of Science Ebook Innovation Based on Project-Based Learning (PjBL) can enhance the critical thinking skills of students. It is expected that this research can provide references for future researchers, and innovations related to interactive teaching materials can be developed not only for one subject but for all subjects in middle school science.